2008
DOI: 10.4161/cc.6552
|View full text |Cite
|
Sign up to set email alerts
|

Checkpoint response plays a more protective role in HZE particle-irradiated cells than in X ray-irradiated cells

Abstract: High linear energy transfer (LET) ionizing radiation (IR) kills more cells as compared with low LET IR at the same doses. High LET IR is induced by high-charge (HZE) particles (a component in space radiation), high energy ions or by a special clinical radiotherapy machine. Low LET IR includes X or γ ray (a major component of IR from standard clinical radiotherapy machines), etc. The more cell death induced by high LET IR than by low LET IR at the same dose reflects a relative biological effectiveness (RBE). RB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
2
6
0
Order By: Relevance
“…Previously our group as well as other groups have shown that the enhanced relative biological effectiveness (RBE) on survival in high-LET irradiated cells is via interfering with NHEJ (Lind et al 2003, Okayasu 2006, Wang et al 2008), but not via affecting HRR (Wang et al 2008, Wang et al 2010, Zafar et al 2010). These results indicate that high-LET irradiated cells depend more on HRR to repair DNA DSB and maintain their survival.…”
Section: Both Sldr and Pldr Depend Mainly On Nhejmentioning
confidence: 93%
See 1 more Smart Citation
“…Previously our group as well as other groups have shown that the enhanced relative biological effectiveness (RBE) on survival in high-LET irradiated cells is via interfering with NHEJ (Lind et al 2003, Okayasu 2006, Wang et al 2008), but not via affecting HRR (Wang et al 2008, Wang et al 2010, Zafar et al 2010). These results indicate that high-LET irradiated cells depend more on HRR to repair DNA DSB and maintain their survival.…”
Section: Both Sldr and Pldr Depend Mainly On Nhejmentioning
confidence: 93%
“…These results indicate that high-LET irradiated cells depend more on HRR to repair DNA DSB and maintain their survival. We have observed that cells deficient in HRR are more sensitive to high-LET IR and showed higher RBE on their survival versus wild type cells (Wang et al 2008). These results provide additional evidence to support that HRR does not affect PLDR.…”
Section: Both Sldr and Pldr Depend Mainly On Nhejmentioning
confidence: 99%
“…These short DNA DSB fragments could prevent Ku from binding efficiently to the two ends of DNA at the same time and delay Ku-dependent NHEJ (2) because Ku binding to DNA DSBs is the first step in NHEJ, which serves to recruit other essential NHEJ factors to the site of DNA DSBs. Since the checkpoint activation is believed to facilitate mainly the HRR and has little effect on NHEJ (3)(4)(5)(6)(7)(8), this means that checkpoint regulation plays a more protective role in high-LET-irradiated cells than in low-LET-irradiated cells (9).…”
Section: Introductionmentioning
confidence: 99%
“…18 This conclusion is derived from the following facts: (1) high-LET radiation kills more cells than low-LET radiation at the same dose due to the inefficient Ku-dependent nonhomologous end-joining (NHEJ) 19 and thus results in HRR playing a more important role in protecting cells from high- than from low-LET IR-induced killing; (2) the CHK1 pathway protects cells from radiation-induced killing through promoting HRR. 13,14 Based on these results, we initially predicted that the small peptide should show an increased protective role in high-LET irradiated cells than in low-LET irradiated cells.…”
Section: Resultsmentioning
confidence: 99%